Exploring Middle School Students' Challenges in Mathematical Literacy: A Study on AKM Problem-Solving - Wahyuni, Astri; Muhaimin, Lukman Hakim; Hendriyanto, Agus; Tririnika, Yuliana (STAI Hubbulwathan Duri, 2024)
Mathematical literacy is the ability to formulate, apply, and interpret everyday problems. The Minimum Competency Assessment (AKM) program in Indonesia is designed to evaluate these essential skills, similar to the PISA framework. Assessing mathematical literacy through the AKM ensures that students meet basic competency standards, helping to improve overall educational quality and better preparing students for global competition. This research reveals the characteristics of students' mathematical literacy when solving AKM problems. The study was conducted at a junior high school in Surakarta, Indonesia. The research stages included giving AKM problems, observing students' problem-solving processes through think-aloud methods, conducting interviews for confirmation, reducing data, coding data, analyzing data, and drawing conclusions. The data used included students' answers, observation sheets, and interview transcripts. When formulating problems, students often struggle to accurately understand the issues at hand. This leads to incomplete data during the problem-solving process, resulting in calculation errors or mistakes in applying formulas. These errors create a domino effect, leading to incorrect answers. Students' difficulties in formulating mathematical problems can potentially cause calculation errors and improper use of formulas, ultimately leading to incorrect solutions. This negatively impacts their conceptual understanding, learning motivation, and readiness to face educational challenges or enter the workforce. To address these difficulties, teachers can enhance students' conceptual understanding, promote critical thinking, implement problem-based learning, use visual aids, provide targeted support, and focus on developing mathematical literacy from an early age.